2013
DOI: 10.2217/pgs.12.197
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Pharmacists‘ Expectations Towards Pharmacogenomics

Abstract: Pharmacists are extremely hopeful towards pharmacogenomic testing. Furthermore, a vast majority is willing to integrate these tests as part of their clinical practice. Proper education will be required if the integration of pharmacogenomics in patient care is to be optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 46 publications
7
90
0
Order By: Relevance
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies have had a response rate of less than 60% for pharmacists, 12,15,16,18,19,23 while the remaining six have response rate more than 60%, 9,17,21,22,25 Only three researches used statistical analysis in questionnaire validation; 12,18,21 two studies used pilot study to validate the questionnaire in the studies; 17,19 majority of studies used experts reviews or kept silence on validity of questionnaire. 9,15,16,[22][23][24][25][26] In total 4,624 pharmacists participated in the reviewed articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Additional studies with medical students in the US and in the UK indicate that they also share the same concerns. 41 Students who participated in this study reported an increased level of confidence with respect to their knowledge base.…”
Section: (89) 7 (11)mentioning
confidence: 99%
“…41 Students who participated in this study reported an increased level of confidence with respect to their knowledge base. As mentioned in the introduction, previous studies have shown that pharmacists were not aware of the pharmacogenomics information in FDA labeling, 40 which was one of the reasons for incorporating a team activity involving FDA and CPIC recommendations 42 as part of the course design.…”
Section: (89) 7 (11)mentioning
confidence: 99%